2005
DOI: 10.2134/jeq2004.0274
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and Transport of Radioactive Nickel and Cadmium into Three Vegetables after Wet Aerial Contamination

Abstract: Knowledge of radionuclide or trace element retention and translocation to plants following an aerial contamination event, for example, sprinkling with contaminated water, is necessary for the evaluation of human exposure through consumption of contaminated vegetables. The fate of 63Ni and 109Cd in all plant parts of three different vegetables after wet deposition on leaves or on fruits was studied. Lettuce (Lactuca sativa L.), radish (Raphanus sativus L.), and bean (Phaseolus vulgaris L.) grown under controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 28 publications
(46 reference statements)
1
12
0
1
Order By: Relevance
“…The results indicated high efficiency of washing of the leaves as well as relatively low impact of PM amendment on total Cd contents in the leaves. Low migration of Cd throughout the whole lettuce plant after foliar Cd application was observed by Fismes et al [27]. Atmospheric deposition of cadmium on herbage from long-term experimental plots at the Rothamsted Experimental Station in the UK was evaluated by Nicholson et al [28].…”
Section: Cadmiummentioning
confidence: 98%
“…The results indicated high efficiency of washing of the leaves as well as relatively low impact of PM amendment on total Cd contents in the leaves. Low migration of Cd throughout the whole lettuce plant after foliar Cd application was observed by Fismes et al [27]. Atmospheric deposition of cadmium on herbage from long-term experimental plots at the Rothamsted Experimental Station in the UK was evaluated by Nicholson et al [28].…”
Section: Cadmiummentioning
confidence: 98%
“…Using data available for Cd and Pb allowed to include these elements into one of these three categories. Thus, Fismes et al (2005) experimentally studied the distribution of radioactive isotope of Cd within three different vegetables, including lettuce and bean. They observed that Cd migrated slightly and that the translocation factor was lower than 10%.…”
Section: Translocation To Edible Parts Of Fruit Vegetablesmentioning
confidence: 99%
“…Despite the fact that both Cd and Ni are divalent and are unable to catalyse the production of reactive oxygen species (ROS) via Fenton-Haber-Weiss reaction, Cd shows more toxic effects in comparison to Ni when applied in equal doses: the main reason for such different toxic effect could be higher endogenous Cd accumulation [12,13]. Besides, Cd and Ni showed different translocation pattern in three crops [14]. Foliar application of identical concentrations is therefore suitable tool allowing to compare if different Cd and Ni toxicity is influenced by physicochemical properties of these metals or by endogenous factors in the given plant species.…”
Section: Introductionmentioning
confidence: 99%